Field-based fitness measures improve via an immersive virtual reality exergaming platform: a randomized controlled trial - Mologne, Mitchell S.; Yamamoto, Trent; Viggiano, Michael; Blatney, August E.; Lechner, Ross J.; Nguyen, Thalia H.; Doyle, Aaron; Farrales, Jason P.; Neufeld, Eric V.; Dolezal, Brett A. (Frontiers in Virtual Reality, 2024)
While there has been a recent onslaught of traditional lab-based fitness measures in immersive virtual reality (IVR) exergaming research, there remains a paucity in the field-based fitness domain, which refers to assessments made outside a formal laboratory setting which are easier, cheaper, and have more practical application. This study aimed to assess changes in field-based fitness tests including the 1mile run, 20-meter dash, multiple single-leg hop-stabilization test, Abalakov jump, and 5-10-5 Pro Agility test during a 1-month workout protocol and to compare differences between groups assigned to either an IVR machine-directed exergaming platform or a traditional, self-directed cable-resistance training control (SELF). Eighteen (7 females) college-aged participants with little resistance training experience were randomized to IVR or SELF and worked out thrice weekly for 4 weeks (12 sessions). Wilcoxon rank-sum tests were performed for continuous variables to assess significance. Compared to SELF, the IVR group had significantly better performance improvements in 20m dash (-0.1s vs 0.0s, p=0.022), 5-10-5 Pro Agility Test (-0.1s vs -0.0s, p=0.003), Abalakov Jump (5.8 cm vs 2.0 cm, p=0.0013), 1-Mile Run (-11.0s vs -2.0s, p=0.008), and Multiple Single-Leg Hop-Stabilization Test with their dominant (-9.0s vs 1.0s, p=0.0015) and non-dominant (-8.0s vs 1.0s, p=0.003) legs. This training study demonstrates that IVR exergaming, more so than those that traditionally resistance train (SELF), can improve many field-based fitness components including agility, balance and stability, speed/acceleration, cardiovascular endurance, and lower-body power.